Matriks Analisis Data Kualitatif Manual (MADKM):Kerangka Operasional Integratif dalam Riset Sosial Kontemporer - Obi Pratama (Yayasan Al-Afif, 2026)
Qualitative data analysis constitutes the core of qualitative research; however, methodological traditions often develop in isolation, making it difficult for researchers to establish transparent and systematic analytical procedures. This study aims to develop the Manual Qualitative data analysis Matrix (MADKM) as an integrative operational framework that bridges the transformation of raw data into research findings. Employing an integrative methodological synthesis approach, the study synthesizes major traditions in qualitative data analysis, including interactive analysis, coding analysis, thematic analysis, framework analysis, and audit trail approaches. The findings reveal a conceptual fragmentation within the qualitative analysis literature, where data reduction, coding, categorization, theme development, data display, and analytical transparency are frequently discussed as separate methodological components. In response to this gap, the study proposes MADKM, which consists of six interconnected stages: raw data, coding, categorization, themes, analytical findings, and conclusions. The framework provides a traceable analytical pathway that strengthens transparency and consistency throughout the qualitative research process. The study concludes that MADKM contributes as an integrative operational framework that consolidates diverse traditions of qualitative data analysis into a practical manual format suitable for contemporary social research.